2020
DOI: 10.1007/s00454-020-00219-7
|View full text |Cite
|
Sign up to set email alerts
|

Near-Optimal Algorithms for Shortest Paths in Weighted Unit-Disk Graphs

Abstract: We revisit a classical graph-theoretic problem, the single-source shortest-path (SSSP) problem, in weighted unit-disk graphs. We first propose an exact (and deterministic) algorithm which solves the problem in O(n log 2 n) time using linear space, where n is the number of the vertices of the graph. This significantly improves the previous deterministic algorithm by Cabello and Jejčič [CGTA'15] which uses O(n 1+δ ) time and O(n 1+δ ) space (for any small constant δ > 0) and the previous randomized algorithm b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Consider next the case where we stop because of the second condition, namely T contains 6 We remark that, unfortunately, this is not the case with the decision procedures used in Wang and Zhao [21] and in Wang and Xue [20] for the reverse shortest-path problem in unit-disk graphs and for its weighted variant. We will modify these procedures, in Sections 3.1, 3.2, and 3.4, to fit into this setup.…”
Section: Bifurcation-tree Constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consider next the case where we stop because of the second condition, namely T contains 6 We remark that, unfortunately, this is not the case with the decision procedures used in Wang and Zhao [21] and in Wang and Xue [20] for the reverse shortest-path problem in unit-disk graphs and for its weighted variant. We will modify these procedures, in Sections 3.1, 3.2, and 3.4, to fit into this setup.…”
Section: Bifurcation-tree Constructionmentioning
confidence: 99%
“…The decision procedure for this problem has been studied by Wang and Xue [20], who showed that, for a given r and a source point s, all shortest paths in G(r) from s to the other points of P can be computed in O(n log 2 n) time.…”
Section: The Reverse Weighted Shortest Path Problem For Unit-disk Graphsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our new structures give improved bounds almost in a black-box fashion, using the respective techniques of Cabello and Jejčič [10] and of Roditty and Segal [46]. Very recently, Wang and Xue [51] presented a deterministic algorithm to find the shortest-path tree in a unit disk graph in O(n log 2 n) time. The other two applications are a bit more involved.…”
Section: Problem Old Bound New Boundmentioning
confidence: 99%